When the Kunlun fault began its left-lateral strike-slip faulting in the northern Tibet: Evidence from cumulative offsets of basement rocks and geomorphic features - Fu, Bihong; Awata, Yasuo (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 132